Pemanfaatan Abu Terbang (Fly Ash) Sebagai Bahan Subtitusi Semen Pada Sebagian Sifat Beton Segar Dan Beton Keras - Panjaitan, Aprizal; Djauhari, Zulfikar; Kurniawandy, Alex (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The research aims to obtain the characteristic of fresh and hard concrete using fly ash as substitute material on normal concrete. It is focused on analyzing the bulk density, workability, setting time, permeability and sulfate resistance. The percentage of fly ash waste that is used are 0% and 30% of the weight of the cement. The results show that using 30% of fly ash decrease the workability and bulk density on concrete. Meanwhile, the setting time with 30% of fly ashsubstitution is faster compared to 0% fly ash substitution. The use of 30% fly ash also increase the value of permeability on those concrete. At the testing of sulfate resistance, concrete with 0% of fly ash increases the compressive strength at ageof 28 and 56 days, then will decrease at the age of 90 days. Meanwhile, for 30 % of fly ash, the compressive strength decreases at the age of 56 and 90 days.Keywords : fly ash, bulk density, workability, setting time, permeability, sulfate resistance